Green Intellectual Capital: Salah Satu Penentu Keunggulan Bersaing Pada UMKM di Serangan - Ni Kadek Nanda Claudia Winyanti; Ni Luh Putu Widhiastuti; Sagung Oka Pradnyawati; Kadek Indah Kusuma Dewi; Ni Putu Wulan Regina Utami (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Competitive Advantage is the ability to do something better so that you have an advantage over your competitors. These advantages make MSMEs have their own place for their customers (stakeholders). This research aims to examine the influence of green human capital, green structural capital and green relational capital on competitive advantage. The population of this research is MSMEs in Attack and the sample is 123 respondents. The sampling technique uses non-probability sampling techniques, precisely saturated sampling. The data analysis used is multiple linear regression analysis. Based on the test results, it is concluded that green human capital and green structural capital have no effect on the competitive advantage of MSMEs in Attack. Meanwhile, green relational capital has a positive influence on the competitive advantage of MSMEs in Attack. Further research can be carried out by adding other variables such as management ability, market orientation and training